A Conceptual Model for Eliciting Mental Models Using a Composite Methodology. (June 2015) - Grenier, Robin S.; Dudzinska-Przesmitzki, Dana
Formed through experience, observation, and learning, mental models are used in decision making to understand, predict, and solve problems. The investigation and application of mental models research are a growing area of scholarly inquiry in human resource development (HRD) and adult education, yet debate about how to best elicit such knowing still persists. Therefore, exemplars for eliciting the mental models of individuals are a matter of importance. The goal of this article is to address some of the issues central to mental model research and the methodological problems faced by scholars and provide an approach to mental model elicitation that holds promise for attending to some of the issues raised in the article. Multi-method Mental Model Elicitation (MMME) overcomes some of the limitations of current approaches, thus helping to increase the utility of mental models research in the field of HRD.